Tinjauan Hukum Ekonomi Syari’ah Tentang Proses Take Over Pembiayaan Kredit Pemilikan Rumah Antar Nasabah Dengan Nasabah - Sulthonuddin, Bung Hijaj; Nuraida, Lisna (STAI Al Musaddadiyah Garut, 2024)
A house is a necessity, so there are various ways to do it, one of which is by taking over mortgage financing. For example, they carry out house buying and selling transactions by taking over mortgage financing using non-official methods without involving developers, only between new and old customers and usually done in front of a notary. The formulation of the problem in this research is how to process and review Sharia Economic Law regarding Take Over mortgage financing in the Suci Village Housing District. Karangpawitan District. Garut? The aim is to find out the KPR financing Take Over process and its laws in Sharia Economics in Suci Village Housing District. Karangpawitan District. Garut. This research includes field research with a qualitative approach. The results of the research show that Take Over mortgage financing in Suci Village Housing District, Kec. Karangpawitan District. Garut is a type of Take Over under the hand using the Hawalah contract, so it is not in accordance with sharia as in the DSN-MUI fatwa No. 12/DSN-MUI/IV/2000, it does not fulfill the requirements and harmony of hawalah and if it is found out, you will be fined. What is in accordance with sharia is official Take Over such as Inter-Bank Take Over and Buy and Sell Take Over Keywords : Shari’ah Economic Law, Take Over, KPR